Organisational Image's Moderating Effect on Cynicism and Turnover Intentions in Public Sector Employees - Budiyanti, Riana; Purwono, Rudi; Margono, Hendro; Teofilus, Teofilus (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study examines the relationship between organizational cynicism and the intention to leave an organization, emphasizing the moderating role of corporate image. The research explores how organizational cynicism impacts an employee's desire to leave, focusing on how the organization's image might influence this relationship. This study fills a gap by specifically analyzing the interplay of these elements, especially among public sector employees in Indonesia. In this study, the perceived external prestige was an indicator of organizational image. A survey was conducted with 80 public sector employees from a government agency in a district in Indonesia to collect data for this study. Social exchange theory served as the theoretical framework of the investigation. The data were then analyzed using Moderated Regression Analysis to determine the regression coefficients, followed by a two-way interaction ANOVA test. According to the data, cynicism is a major predictor of the desire to leave the organization, and organizational image helps mitigate the link between cynicism and intention to leave. This study contributes to the existing body of knowledge by shedding light on the influence of adverse workplace perceptions on employees' intentions to leave their employers, particularly in public sector firms. Notable because it analyzes the interplay between these variables, this study stands out. Prior research has not investigated all three components concurrently in the manner proposed by the model.